Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am having a problem with this question.

I need to prove by induction that: $$\sum_{k=1}^n \sin(kx)=\frac{\sin(\frac{n+1}{2}x)\sin(\frac{n}{2}x)}{\sin(\frac{x}{2})}$$

The relation is obvious for n=1

Now I suppose that the relation is true for a natural number n and I want to show that $$\sum_{k=1}^{n+1} \sin(kx)=\frac{\sin(\frac{n+2}{2}x)\sin(\frac{n+1}{2}x)}{\sin(\frac{x}{2})}$$

We have $$\sum_{k=1}^{n+1} \sin(kx)=\sin[(n+1)x]+\sum_{k=1}^{n} \sin(kx) =\sin[(n+1)x]+\frac{\sin(\frac{n+1}{2}x)\sin(\frac{n}{2}x)}{\sin(\frac{x}{2})}= \frac{\sin[(n+1)x]\sin(\frac{n+1}{2}x)\sin(\frac{n}{2}x)}{\sin(\frac{x}{2})}$$

I am unable to simplify the expression using the trigonometric identities. I keep turning around in circles.

Can somebody help me please.

Thank you in advance

share|cite|improve this question
Why dont you simpliy add $\sin\big((n+1) x\big)$ to both sides of the induction hypotesis? – Pragabhava Oct 29 '12 at 19:25
Why do you think $\sum_{k=1}^{n+1} a_k = a_{n+1}\sum_{k=1}^n a_k$? Shouldn't it be $a_{n+1} + \sum_{k=1}^n a_k$? – Thomas Andrews Oct 29 '12 at 19:31
The last equality is incorrect. It should read $$\frac{\sin[(n+1)x]\sin[\frac{x}{2}] + \sin[\frac{n+1}{2} x]\sin[\frac{n}{2} x]}{\sin[\frac{x}{2}]}$$ – Pragabhava Oct 29 '12 at 20:40
up vote 2 down vote accepted

Sign $"+"$ is missing: $$\sum\limits_{k=1}^{n+1} \sin(kx)=\sin[(n+1)x]\color{red}{+}\sum\limits_{k=1}^{n} \sin(kx) =\sin[(n+1)x]\color{red}{+}\dfrac{\sin(\frac{n+2}{2}x)\sin(\dfrac{n+1}{2}x)}{\sin(\dfrac{x}{2})}=\ldots$$

share|cite|improve this answer

You can actually use telescopy, which is just induction in disguise.

We have that

$$\cos b - \cos a = 2\sin \frac{{a + b}}{2}\sin \frac{{a - b}}{2}$$ Now let $$b=\left(k+\frac 1 2 \right)x$$ $$b=\left(k-\frac 1 2 \right)x$$


$$\cos \left( {k + \frac{1}{2}} \right)x - \cos \left( {k - \frac{1}{2}} \right)x = 2\sin kx\sin \frac{x}{2}$$

Now sum through $k=1,\dots,n$, to get

$$\sum\limits_{k = 1}^n {\cos \left( {k + \frac{1}{2}} \right)x - \cos \left( {k - \frac{1}{2}} \right)x} = 2\sin \frac{x}{2}\sum\limits_{k = 1}^n {\sin kx} $$

$$\cos \left( {n + \frac{1}{2}} \right)x - \cos \frac{x}{2} = 2\sin \frac{x}{2}\sum\limits_{k = 1}^n {\sin kx} $$


$$\frac{{\cos \left( {n + \frac{1}{2}} \right)x - \cos \frac{x}{2}}}{{2\sin \frac{x}{2}}} = \sum\limits_{k = 1}^n {\sin kx} $$

But using our first formula once more, we have

$$\cos \left( {n + \frac{1}{2}} \right)x - \cos \frac{x}{2} = 2\sin \frac{{\left( {n + 1} \right)x}}{2}\sin \frac{{nx}}{2}$$ so finally

$$\frac{{\sin \frac{{\left( {n + 1} \right)x}}{2}\sin \frac{{nx}}{2}}}{{\sin \frac{x}{2}}} = \sum\limits_{k = 1}^n {\sin kx} $$

as desired.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.